Professional Standards in Medical Ultrasound – EFSUMB Position Paper (Long Version) – General Aspects - Wüstner, Matthias; Radzina, Maija; Calliada, Fabrizio; Cantisani, Vito; Havre, Roald Flesland; Jenderka, Klaus-Vitold; Kabaalioğlu, Adnan; Kocian, Milan; Kollmann, Christian; Künzel, Julian; Lim, Adrian; Maconi, Giovanni; Mitkov, Vladimir; Popescu, Alina; Saftoiu, Adrian; Sidhu, Paul S.; Jenssen, Christian (Ultraschall in der Medizin - European Journal of Ultrasound, 2022)
This first position paper of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) on professional standards presents a common position across the different medical professions within EFSUMB regarding optimal standards for the performing and reporting of ultrasound examinations by any professional ultrasound operator. It describes general aspects of professionality that ensure procedure quality, effectiveness, efficiency, and sustainability in virtually all application fields of medical ultrasound. Recommendations are given related to safety and indication of ultrasound examinations, requirements for examination rooms, structured examination, systematic reporting of results, and management, communication and archiving of ultrasound data. The print version of this article is a short version. The long version is published online.
Keywords: ultrasound; education; training; quality assurance; imaging